1999
DOI: 10.1046/j.1365-2249.1999.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Two polymorphisms of the tumour necrosis factor gene do not influence survival in pancreatic cancer

Abstract: Polymorphisms of the tumour necrosis factor (TNF) gene have been related to TNF production and outcome in a variety of inflammatory and malignant diseases. Proinflammatory cytokines and the inflammatory state appear to affect outcome in pancreatic cancer. Thus, the present study examined the TNFB and TNF-308 polymorphisms for their relationship to the inflammatory state and survival in pancreatic cancer. Sixty-four patients with advanced pancreatic cancer and 101 healthy subjects were genotyped for each polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
3
15
1
1
Order By: Relevance
“…One hundred and eighty-three (83%) patients in our study had lost weight at the time of diagnosis with almost half of these patients losing 10% or more of their pre-illness body weight. Assuming a linear course, the median rate of weight loss was 2.5% body weight per month (approximately 1.9 kg per month) and compares with previous study relating to patients with pancreatic cancer where the mean rate of weight loss was 2.3 kg per month (Barber et al, 1999a;Fearon et al, 2003). Pancreatic cancer is notorious for its association with marked weight loss (DeWys et al, 1980;Galizia et al, 2002).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…One hundred and eighty-three (83%) patients in our study had lost weight at the time of diagnosis with almost half of these patients losing 10% or more of their pre-illness body weight. Assuming a linear course, the median rate of weight loss was 2.5% body weight per month (approximately 1.9 kg per month) and compares with previous study relating to patients with pancreatic cancer where the mean rate of weight loss was 2.3 kg per month (Barber et al, 1999a;Fearon et al, 2003). Pancreatic cancer is notorious for its association with marked weight loss (DeWys et al, 1980;Galizia et al, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…Cancer cachexia is associated with reduced quality of life scores, reduced performance status, lower response rates to chemotherapy and overall poorer outcomes (DeWys et al, 1980;Ross et al, 2004;Barber et al, 1999a). Around 20% of deaths from cancer may be directly related to cachexia (Studley, 1936;Inagaki et al, 1974).…”
mentioning
confidence: 99%
“…6 TNF-A expression has been associated with the severity of acute pancreatitis (7) and may play a role in tissue remodeling following chronic pancreatitis (8). However, studies of the TNF-A À308 polymorphism and pancreatitis or pancreatic cancer generally have indicated a lack of association (32,33). Our result may be different in that the association of TNF-A and RANTES with pancreatitis was found mainly among cases of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 55%
“…The homozygous common allele genotype (TNFB*1/ TNFB*1) seems to protect against lung cancer (Shimura et al, 1994), colorectal cancer (Park et al, 1998) and breast cancer (Park et al, 2002). Studies on gastric cancer have also shown a prolonged survival in patients with this genotype (Shimura et al, 1995), whereas no association with either susceptibility or survival was demonstrated in pancreatic cancer (Barber et al, 1999).…”
Section: Tumour Necrosis Factormentioning
confidence: 99%